Mechanical properties of adhesive joints made with pressure-sensitive adhesives - Rudawska, Anna (Strojniški vestnik, 2021)
The paper aims to determine the mechanical properties of the adhesive joints made with acrylic pressure-sensitive adhesives. Two types of double-sided acrylic pressure-sensitive adhesive tapes are used. Three construction materials are used to prepare the adhesive joints: structural steel sheet (C45), aluminium alloy sheet (EN-AW 5754), and titanium sheet (Grade 2). Strength tests of adhesive joints made with the pressure-sensitive adhesive tapes are carried out both after conditioning time at room temperature (23 °C) and subjected to thermal shocks (500 cycles: +60 °C / -40 °C). Strength tests are carried out based on the DIN EN 1465 standard on a Zwick/Roell Z150 testing machine. The main conclusion from the tests carried out was the positive effect of thermal shocks on the mechanical strength of joints bonded with pressure-sensitive adhesive tape.
Keywords: adhesive joints; aluminijeve zlitine; jeklo; lepila; lepljeni spoji; mechanical properties; mehanske lastnosti; pressure-sensitive adhesive; temperaturni šoki; thermal shocks